Childlessness and health seeking behavior in resource poor setting of dang and Udayapur district of Nepal - Gupta, Rajani; Adhikari, Renu; Rishal, Poonam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Childlessness is not problem in resource-poor area where fertility rates are high. The consequence of childlessness is very severe in low-income countries like Nepal, particularly for women. Childless women are frequently stigmatized, isolated, ostracized, disinherited and neglected by the family and local community. This may result in physical and psychological abuse, polygamy and even suicide. The aim of the study is to explore the perception of childlessness, its cause and consequences and health seeking behavior among couples in order to develop strategies for action and policy-setting. Methods: This was a qualitative study conducted in Dang and Udayapur district of Nepal. Childlessness couple were recruited through snowball sampling. Information was also gathered from key informant and Focus group discussion. All interview were audiotaped using a digital recorder. Results: Women expressed that they are being discriminated, humiliated and intimated by their family members and society for being childlessness. Despite childlessness problem with husband, women experience emotional and physical abuse. Financial constraints and unaffordable service as one of the major problems among couple that led to withdrawal or stop attending their follow up for modern treatment. Conclusions: The study concludes that childlessness women suffer from all spare of their personal and social life although childlessness is a biomedical cause. Financial hardship and family pressure made them to seek traditional healer for first treatment approach for childlessness rather than modern method of treatment. Therefore, childlessness needs to be seen as a public health issue rather than a pure medical condition. Hence, multi-sectoral (i.e., Preventive, promotive and social dimension) response to address childlessness could be valuable.